Gastrointestinal Parasite Infections in Sheep from Torghondi, Islam Qala, and the Herat Slaughterhouse - Tookhy, Nazir Ahmad; Bui, Dung Thi; Haidari, Esmatullah; Shakhes, Shoaib Ahmad; Nasiry, Zabihullah; Mohmand, Noor Ali; Pooyan, Abdul Qader; Haqmal, Mohammad Aman (Universitas Airlangga, 2025)
Gastrointestinal parasites (GIPs) pose significant health and productivity challenges to livestock, especially in regions with limited veterinary care and extensive farming practices. This study evaluated the prevalence of GIPs in sheep at the Torghondi and Islam Qala borders, as well as the Herat Slaughterhouse. A total of 450 faecal samples were examined microscopically, and 200 gastrointestinal tract samples (including stomach and intestinal contents) were analysed by dissection. The overall faecal infection rate was 77.3%, with prevalence rates of 76.7% at Torghondi, 90% at Islam Qala, and 65.3% at Herat Slaughterhouse. Eimeria spp. was the most prevalent parasite, detected in 73.7% of faecal samples. Nematodes (Nematodirus spp., Trichuris spp., Strongyle spp.) and trematodes (Amphistome spp.) were also identified. Gastrointestinal tract analysis revealed Trichuris spp. in 40.5% and Moniezia spp. in 37.5% of the samples. These findings highlight the roles of climate, livestock management, and environmental conditions on the distribution of GIPs. The high prevalence of parasites underlines the urgent need for effective control measures, including regular deworming, improved sanitation, and enhanced biosecurity practices. Future research should identify specific risk factors to inform targeted interventions and improve regional livestock health.